MPX3 van der Waals magnets under pressure (M = Mn, Ni, V, Fe, Co, Cd; X = S, Se) - Matsuoka, Takahiro; Kim, Heung-Sik; Samanta, Subhasis; Musfeldt, Janice L.; Mandrus, David G. (Frontiers in Materials, 2024)
van der Waals antiferromagnets with chemical formula MPX 3 (M = V, Mn, Fe, Co, Ni, Cd; X = S, Se) are superb platforms for exploring the fundamental properties of complex chalcogenides, revealing their structure-property relations, and unraveling the physics of confinement. Pressure is extremely effective as an external stimulus, able to tune properties and drive new states of matter. In this review, we summarize experimental and theoretical progress to date with special emphasis on the structural, magnetic, and optical properties of the MPX 3 family of materials.Under compression, these compounds host inter-layer sliding and insulator-to-metal transitions accompanied by dramatic volume reduction and spin state collapse, piezochromism, possible polar metal and orbital Mott phases, as well as superconductivity. Some responses are already providing the basis for spintronic, magneto-optic, and thermoelectric devices. We propose that strain may drive similar functionality in these materials.